Bcl-2 expression in cell lines breast cancer and death program: Bcl-2 expression in breast cancer - Janaghard, Mohsen Sedaghat; Soleimani, Shahrzad; Movafagh, Abolfazl; Motallebi, Marzieh; Mousavi, Seyede Amenh; Moghadam , Ali Akbar Saffar; Moghadam, Vahid Erfani; Khosravi, Ayoob; Mirzaei, Hamid Reza; Mousavi, Seyed Ali Reza; Aziziaram, Zahra; Sun, Chenghui (Cellular and Molecular Biology, 2023)
Breast cancer is a hormone-dependence and heterogenic disease. Drug resistance is the main reason for the failure of breast cancer treatment. Combinatory medications are methods for treatment but they are not sufficient in action. However, new approaches like molecular therapy reveal a new insight into cancer treatment. Studies show that Bcl-2 gene family inhibitors and ER blockers cause the improvement of recovery. Interfering molecules such as antisense ones can inhibit the expression of Bcl-2 and push the cancer cells to apoptosis. Our team designed a new Antisense Oligonucleotide (ASO) based on Antisense oligo G3139. MCF-7 and MDA-MB-231 cell lines were used to evaluate cellular proliferation. Liposomes and cationic nano-complex (Niosome) are used to increase the cellular delivery of ASO and Tamoxifen. We also investigated the cytotoxicity and apoptotic effects of Tamoxifen, naked ASO and Nano-packed ASO. The results indicated significant down-regulation of the Bcl-2 gene and inhibition of MCF-7 and MDA-MB-231 cellular proliferation. Flow-cytometry showed early apoptosis in all cell groups. The newly designed ASO reduced the expression of the Bcl-2 gene. It also had a synergistic effect with the Tamoxifen. The cationic nano-complex (Niosome) was more efficient than the liposome in delivering designed oligo antisense Bcl-2 in the cancer cells.